IN THE FOOTSTEPS OF WENDELL C. BENNETT IN THE BASIN LAKE TITICACA - Flores, Luis A. (2015)
According to many researchers Wendell C. Bennett was the most important archaeologist of his time abroad. His profuse work led to it being considered as one of the founders of the Bolivian archaeological research. However, their contribution has been little considered in Peru, despite its many excavations in the valleys of Lambayeque and La Libertad; as well as iconic sites like Chavin and Huari. This rich information escapes our article, which will focus only on highlighting its work in the Lake Titicaca, considering excavated in key places like Tiwanaku and Chiripa, the first systematized information for this region. It is proposed that their approaches are still in place, often covertly in the interpretations of archaeologists interested in the highland region. Even their formulations achieved pan-Andean trim with its proposed ceremonial centers and Co-Tradition.